I vetri del Museo Archeologico di Tripoli - Cingolani, Sofia (Archaeopress Roman archaeology, 2015)
This volume is focused on the cataloguing of glass conserved in the Archaeological Museum of Tripoli. This is so far an unpublished corpus of objects identified from investigations into the necropolis and other burials in Tripoli and its suburbs, in conjunction with the activities of the Italian Government in Libya during the first twenty years of the last century. The main objective of the work is filling the gaps in the state of knowledge concerning the production of glass of the North-African area by providing as complete as possible a documentation on the findings from Oea and its territory.